Seed germination and growth of Joseph’s coat (Amaranthus tricolor L.) following exposure with Naphthalene-1-Acetic Acid (NAA) and 2,4-Dichlorophenoxyacetic Acid (2,4-D) - Ilmam, Hadyan Pratama Lutfi; Dewi, Kumala (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
Amaranthaceae is a family of plants that can be used as vegetables and medicinal herbs. Amaranthus tricolor L. is commonly cultivated because it has fast growth rate and short life cycle that can be boosted by growth regulators such as auxins. A. tricolor L. is commonly cultivated because it has a fast growth rate and short life cycle. Growth regulators, such as auxins, can boost the growing process. This research aimed to study the effects of Naphthalene-1-Acetic Acid (NAA) and 2,4-Dichlorophenoxyacetic Acid (2,4-D) on the seed germination and growth of A. tricolor L. and to determine effective concentration of NAA or 2,4-D application to A. tricolor L. This research was arranged in a completely randomized design with exogenous hormones application as treatments. The treatments consisted of various concentrations of NAA and 2,4 D (0 ppm, 10 ppm, 20 ppm, 40 ppm, and 80 ppm) applied to A. tricolor L. plants every two weeks. Germination test of A. tricolor L. was carried out for 14 days, and the application of NAA and 2,4-D on A. tricolor L. plant was given for 56 days. Observations were made on the plant height, fresh and dry weight, stomatal density, and the content of chlorophyll and carotenoid. Data analysis was conducted using one-way analysis of variance and Duncan Multiple Range Test (DMRT) with significance level of 5%. NAA treatment delayed seed germination by one day compared to control, while 2,4-D treatment inhibited germination for several days with the higher concentration of 2,4-D applied, the greater inhibition of seed germination. NAA of 10 ppm increased plant height, fresh and dry weight, chlorophyll content, and leaf area of A. tricolor L. The application of NAA and 2,4-D reduced stomatal density and carotenoid content of A. tricolor L., with greater effects at higher concentrations of synthetic auxins. This research concluded that NAA or 2,4-D inhibited germination of A. tricolor L. seeds, NAA of 10 ppm effectively increased plant growth and chlorophyll content, but higher NAA concentrations inhibited growth. Application of 2,4-D with concentrations above 40 ppm could be lethal for A. tricolor L.